Critical literacy in literature education - Skaftun, Atle; Sønneland, Margrethe (Acta Didactica Norden, 2022)
In this article we discuss literature education as an opportunity space for critical literacy, based on a set of principles derived from the pedagogy of Paolo Freire. These principles are highly compatible with the development of Norwegian curricula in our millennium. We start by establishing the connection between Freire’s ideas and the latest Norwegian curricular reform, Fagfornyelsen (implemented in 2020), emphasizing the concept of literacy as an important link between the two, before pursuing Freire and Macedo’s (1987) understanding of literacy as reading not only the word, but also the world. This conception of literacy implies a literacy education where the relationship between the learner and the world is the pivotal point. We interpret this relationship as an interface between the learner engaged in the world and the world presented as a problem, before turning to a case of problem oriented literature education in lower secondary school. In conclusion, we remind ourselves and educational researchers about the deep connectivity between humanist and literary theories and methodologies, and we suggest that making space for students to encounter texts presented as open-ended problems, represents a productive path towards critical literacy and, consequently, towards revitalizing literature education.